2014
DOI: 10.1186/1471-2318-14-85
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the evidence that brain structure is related to muscle structure and their relationship to brain and muscle function in humans over the lifecourse

Abstract: BackgroundAn association between cognition and physical function has been shown to exist but the roles of muscle and brain structure in this relationship are not fully understood. A greater understanding of these relationships may lead to identification of the underlying mechanisms in this important area of research. This systematic review examines the evidence for whether: a) brain structure is related to muscle structure; b) brain structure is related to muscle function; and c) brain function is related to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 107 publications
8
53
0
3
Order By: Relevance
“…The main cortical activation regions for processing conceptual and spatial information for ADL include the ventral frontal cortices and anterior cingulate cortex (Stamatovic, Brandi, Goldenberg, Hughes, & Hermsdörfer, 2014). Several studies have also demonstrated that the ventromedial prefrontal cortex, caudolateral orbitofrontal cortex, insular cortex, and corpus callosum are involved in muscle function (Kilgour et al., 2014), which is critical for ADL. In addition, focal frontal lesions or pathological changes impair ADL (Godbout, Grenier, Braun, & Gagnon, 2005; Marshall, Fairbanks, Tekin, Vinters, & Cummings, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main cortical activation regions for processing conceptual and spatial information for ADL include the ventral frontal cortices and anterior cingulate cortex (Stamatovic, Brandi, Goldenberg, Hughes, & Hermsdörfer, 2014). Several studies have also demonstrated that the ventromedial prefrontal cortex, caudolateral orbitofrontal cortex, insular cortex, and corpus callosum are involved in muscle function (Kilgour et al., 2014), which is critical for ADL. In addition, focal frontal lesions or pathological changes impair ADL (Godbout, Grenier, Braun, & Gagnon, 2005; Marshall, Fairbanks, Tekin, Vinters, & Cummings, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermetabolism is linked to disability and cognitive dysfunction (Claassen et al., 2002). Previous studies have demonstrated that white matter (WM) hyperintensity is associated with muscle function (Kilgour, Todd, & Starr, 2014) and that docosahexaenoic acid improves short‐ and long‐term neurological performance as well as reduces cerebral edema (Schober et al., 2016). Therefore, we hypothesized that vasogenic cerebral edema may contribute to the impairment in the performance of ADL in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relationship between physical activity and inhibition of cognitive decline might not depend on the improved fitness. Physical activity and cognitive function might be regulated not only by muscle function but also by brain volume and systemic blood flow (20,21). Therefore, it is conceivable that a mixture of MCTs, leucine, and cholecalciferol affects brain volume (or brain function) and systemic blood flow by unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The common element between the constructs of frailty and SPPB is gait speed as measured by timed gait. In a recent review of 27 studies examining gait speed in relation to structural brain findings on MRI, numerous associations between gait speed and white and gray matter volume have been observed, but the evidence base is quite mixed and inconsistent [5]. For example, in the Cardiovascular Health Study, slower gait speed and faster decline in gait speed were associated with ventricular enlargement and white matter hyperintensities on MR [32,33], but confirmatory evidence is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults rely on more regions of their brain for movement than younger people [4]. Lower grip strength and gait speed have been associated with markers of brain aging including brain atrophy and white matter hyperintensities [5]. However, the role of brain pathology in driving declines in physical function is virtually unknown.…”
Section: Introductionmentioning
confidence: 99%